Light gap forest - Kamarudin, Norizah; Abdul Aziz, Nor Akmar; Jamaluddin, Jamhuri; Mohd Saad, Mohamad Ridzuan; Lukhman, Arief Aiman; Parman, Rhyma Purnamasayangsukasih (Universiti Putra Malaysia Press, 2017)
When an individual or large clumps of trees are removed from a forest, a hole is formed in the forest canopy. Trees may be removed due to harvesting, or because they are damaged by wildfire or diseases, or succumb to old age. The resulting hole in the canopy is known as a ‘light gap’ because more direct sunlight reaches the forest floor in contrast to the usual one to five percent under full canopy conditions.